2010
DOI: 10.1016/j.brainres.2009.10.075
|View full text |Cite
|
Sign up to set email alerts
|

Exercise exerts neuroprotective effects on Parkinson's disease model of rats

Abstract: Recent studies demonstrate that rehabilitation ameliorates physical and cognitive impairments of patients with stroke, spinal cord injury, and other neurological diseases and that rehabilitation also has potencies to modulate brain plasticity. Here we examined the effects of compulsive exercise on Parkinson's disease model of rats. Before 6-hydroxydopamine (6-OHDA, 20 microg) lesion into the right striatum of female SD rats, bromodeoxyuridine (BrdU) was injected to label the proliferating cells. Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
178
0
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(212 citation statements)
references
References 33 publications
15
178
0
19
Order By: Relevance
“…Experiments in animal models of PD have shown that exercise can improve motor function and have a neuroprotective effect (Fisher et al, 2004;Petzinger et al, 2007Petzinger et al, , 2013Tajiri et al, 2010;Tillerson et al, 2003;Zigmond et al, 2009). These animal models generally utilize either 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) or 6-hydroxydopamine (6-OHDA) lesioning to induce degeneration of dopaminergic neurons .…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in animal models of PD have shown that exercise can improve motor function and have a neuroprotective effect (Fisher et al, 2004;Petzinger et al, 2007Petzinger et al, , 2013Tajiri et al, 2010;Tillerson et al, 2003;Zigmond et al, 2009). These animal models generally utilize either 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) or 6-hydroxydopamine (6-OHDA) lesioning to induce degeneration of dopaminergic neurons .…”
Section: Introductionmentioning
confidence: 99%
“…Bdnf and Becn1 mRNA expression levels at the spinal cord lesion site of rats in the H-MSC group were significantly higher than those in the Ctrl group. BDNF plays an important role in survival and differentiation of various neural cells types during neural development and after brain injury, which affect functional recovery [34][35][36]. Although BDNF was reported to play a role in regulating VEGF expression [37,38], it has been recently confirmed that BDNF expression and action are dependent on the vascular endothelial growth factor receptor-2 identifying BDNF as a downstream signaling partner of VEGF [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, exercise for 2 weeks after intrastriatal injection of 6-OHDA results in partial recovery of TH labeling and axonal fiber projection to the striatum (Yoon et al, 2007). Treadmill exercise starting the day after intrastriatal 6-OHDA infusion induces significant preservation of TH-positive fibers in the striatum and TH-positive neurons in the substantia nigra pars compacta as compared to the non-exercised group (Tajiri et al, 2010). An increase in TH labeling in the substantia nigra pars compacta of MPTP-treated mice receiving treadmill exercise was also recently reported (B.A.…”
Section: Exercising For Gdnf Expression?mentioning
confidence: 98%
“…These discrepancies might be related to differences in the lesion regimen/extension and exercise paradigm. Physical exercise increases the expression of GDNF in the nigrostriatal system, and this correlates with the protection of dopaminergic neurons against MPTP toxicity (Faherty et al, 2005), and amelioration of motor impairment due to a 6-OHDA lesion (Cohen et al, 2003;Tajiri et al, 2010). Exercise in the running-wheel markedly accelerates spontaneous recovery after a 6-OHDA lesion as animals exercised on the running-wheel prior or after a unilateral striatal 6-OHDA injection show a faster motor recovery compared to nonexercised animals (O'Dell et al, 2007).…”
Section: Exercising For Gdnf Expression?mentioning
confidence: 99%